Intimate Partner Violence and Parenting: Examining the Roles of Parenting Stress, Timing, and Maternal Abuse History - Sypher, Isaiah (Journal of family violence, 2022)
Maternal intimate partner violence (IPV) exposure has been linked to negative parenting outcomes. Studies suggest that parenting stress is an intermediary between IPV exposure and parenting, though past work has relied on small, clinically- referred samples. Moreover, it is unclear if parenting is differentially affected by a mother’s recent versus past history of IPV exposure, or whether a mother’s childhood abuse history moderates the associations of IPV with parenting stress and parenting behaviors. The current study examines whether recent IPV, versus past IPV, has stronger associations with parenting stress and parenting behaviors and tests whether maternal abuse history moderates these associations. Using structural equation modeling, we tested relations between IPV (frequency and recency), parenting stress, and parenting behaviors cross-sectionally and longitudinally in a large community sample of IPV-exposed low-income Hispanic and African American mothers of children aged 0–14 years (N = 1159). We found that mothers who reported IPV exposure in the past year reported higher negative and lower positive parenting behaviors than mothers who reported less recent exposure. Further, we found that the frequency and timing of IPV exposure affected parenting indirectly through increased parenting stress. However, a childhood history of abuse did not appear to sensitize women to these effects. These findings suggest that psychological interventions aimed at reducing the subjective experience of parenting stress, as well as increased access to resources that reduce objective childcare burden, are important for promoting resilience among families exposed to violence.